KEPEMIMPINAN DALAM PERSPEKTIF GENDER SERTA PERANNYA DALAM PENGEMBANGAN BISNIS - Dwi Susanti, Rizki Aprilia; Kusumaning Budi, Citra Setyaniwahyu (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2023)
Historically, male leadership has been more dominant than female leadership. But today, women cannot always be seen as side workers, they are able to make their own choices, especially in business. The role of women sensitive to micro-enterprises in the Indonesian economy is gradually becoming the "gatekeeper" of the people's economy. The method used in this study is a qualitative method with a descriptive approach, this analysis will describe the results of the research based on the findings in the field and then given interpretation and conclusions. The initial stage is grouping the data, and then analyzing it in a qualitative descriptive manner. So that it can produce a scientific understanding and definition to get a systematic picture.There are many great women who become leaders. This research shows that women's leadership styles are more inclined to Transformational Feminism, which is more charismatic and democratic, Efforts to build emotional attachment with employees and patterns of conflict resolution in a familial way, can indirectly make it easier for women to find a win-win solution. In business development there are two strategies applied to Bedpackers Hostel Malang, namely offline and online, such as collaborating with other companies in promoting the Hostel. Meanwhile, in online development, namely through collaboration with Reddoorz, through the website, through Facebook, Instagram. The business development strategy apart from online media to maximize profits Badpackers Hostel Malang also offers various facilities such as Netflix vouchers, promos for guests who book more than three days to one month, dinner in collaboration with restaurants, laundry and online taxis so that they can make customers feel comfortable. hotel guests feel more comfortable.